Rzeczownikowość a czasownikowość kategorii słowotwórczych rzeczownika w języku polskim - Szczyszek, Michał (Investigationes Linguisticae, 2013)
The article has one aim: research correlation between Nisbett’s conception of geography of thought and its linguistic confirmations, on the word-formation level. I analysed word-formation categories of Polish noun. Thesis about Western property of Polish derivative system (and polish thought, categorization) take the confirmation.